Buying and Selling Shares in the Capital Market (Comparative Study of Fatwa Opinions of DSN and Contemporary Fuqaha) - Hulaiva Pary; Jaenudin Jaenudin; Muh. Fauzan Januri (Journal of Islamic Economics Lariba, 2021)
There are many differences of opinion among the scholars in establishing a law itself. This study aims to compare the opinion of fatwa DSN with Fuqaha Kontempore in establishing the law of Buying and Selling Shares. The approach used in this writing is a normative juridical approach. The authors used a qualitative type of research. The result that the author can conclude is that the law of buying and selling shares is permissible it is also forbidden. Among them are opinions according to contemporary fuqaha, some argue that the sale and purchase of legal shares are permissible, and some are forbidden. Meanwhile, according to fatwa DSN, ensuring the transaction of buying and selling halal shares.